Imlementasi SMART-TENDIK PAUD: Inovasi Manajemen Pendidik dan Tenaga Kependidikan Berbasis Refleksi dan Kolaborasi untuk Meningkatkan Profesionalisme Guru PAUD - Loeyyina Khuru’Aini; Hilyatun Naimah; Fetty Ernawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe in detail the implementation of the SMART-TENDIK PAUD innovation as a model for managing educators and educational personnel based on reflection, collaboration, and the use of simple technology, as well as to analyze its impact on improving teacher professionalism in early childhood education settings. This study employs a qualitative approach using a literature review method to explore relevant theories and previous research findings. Data collection techniques include document analysis and systematic online searches from various credible academic sources. Data analysis is conducted through the stages of data reduction, data display, and conclusion drawing to ensure comprehensive and accurate interpretation. The results indicate that the implementation of SMART-TENDIK PAUD enhances teachers’ reflective awareness, strengthens collaboration through active participation in learning communities, and improves the effectiveness of educational personnel management through the practical use of simple and accessible technology. Furthermore, this innovation contributes significantly to improving the quality of learning, making it more creative, adaptive, and innovative. Therefore, SMART-TENDIK PAUD can serve as an alternative model of effective, applicable, and sustainable management innovation in enhancing the professionalism of early childhood education teachers.